Skip to content

Inverse Functions

Given a function, you can inverse it as so that the input of the inverse function is the output of the original function, and the output of the inverse function is the input of the original function.

Inverse Functions are denoted by name^{-1}(inputs...) = output.

Example

Given the function f(x) = 3x + 2, you can work out the inverse with the following procedure:

  • Change the function as equal to y
  • Rearrange the function to make input the subject
  • Swap x out for name(input) and y with input
\begin{align} f(x) & = 3x + 2 \\ y & = 3x + 2 \\ y - 2 & = 3x \\ \frac{y - 2}{3} & = x \\ f^{-1}(x) & = \frac{x - 2}{3} \end{align}

Lets test the function.

\begin{align} f(x) & = 3x + 2 \\ f(3) & = 3(3) + 2 \\ & = 11 \\ \\ f^{-1}(x) & = \frac{x - 2}{3} \\ f^{-1}(11) & = \frac{11 - 2}{3} \\ & = \frac{9}{3} \\ & = 3 \end{align}

Except as otherwise noted, the content of this page is licensed under the Creative Commons Attribution 4.0 License, and code samples are licensed under the Mozilla Public License 2.0.